SWOT Analysis in Developing Zakat at The National Amil Zakat Agency (BAZNAS) Bandung Regency - Intan Nurrachmi; Elisa Siti Widyastuti; Tiya Rissa Kamila; Fahira Febriana Ayuni Destari (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Zakat is one of the pillars of Islamic development and is also one of the pillars of Islamic economic strength. The way of zakat management also affects public trust in a zakat management institution, such as the Bandung City National Amil Zakat Agency (BAZNAS) which has the task of collecting and receiving zakat from muzakki, maintaining it and for that reason, distributing or distributing to mustahiks who have the right to write it. The purpose of zakat management is to increase justice in the distribution of zakat funds, welfare of the community, and to overcome poverty in order to utilize zakat funds to be more productive. So that BAZNAS Bandung Regency should improve zakat management in order to improve the quality of zakat mustahik. This study will review the extent of zakat management in the city of Bandung, which is a non-profit institution in the management and distribution of zakat funds. This research uses a SWOT (Strengths, Weakness, Opportunities, Threats) analysis method with a literature study approach. From the results of the study using the SWOT method, it is stated that in the strength factor (Strengths) and in the weakness factor table the total of all internal variables, namely 2.8 and opportunities (opportunities) shows that the total is greater than threats, the two variables are 2.91. This shows that the opportunities in BAZNAS Bandung Regency are very high compared to the weaknesses and threats that occur. So that if BAZNAS Bandung Regency can take advantage of these opportunities and strengths, BAZNAS Bandung Regency can develop its zakat funds to be even more productive and can improve the welfare of the people of Bandung Regency in particular.